2010
DOI: 10.2478/s11535-010-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and agro-biological diversity of Viburnum opulus genotypes

Abstract: Abstract:Interest in the biochemical composition of Viburnum opulus fruit has intensified due to the food industry's demand for natural vitamins, pigments and other substances that enhance the value of different foods. The present study was conducted to determine the agro-biological and biochemical variability of V. opulus and to select the genotypes that could best serve as sources of health promoting substances. Twelve selected genotypes were evaluated. 'Leningradskaya Otbornaya', V. opulus var. americanum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 32 publications
6
32
3
2
Order By: Relevance
“…The lowest weight found was 0.67 g in the SIV-2 genotype, but it too was not significant relative to the other seedlings. Previously, the weight of European Cranberrybush fruit had been reported between 0.40 and 0.87 g (Bolat and Ozcan 1995, Kara et al 1995, Kollmann and Grubb 2002, Karadeniz et al 2003, Cesoniene et al 2010, Ozrenk et al 2011, Gundogar 2013. Large fruit is a desirable quality trait, primarily for the fresh fruits and secondly for the dried ones, rendering them more attractive to consumers.…”
Section: Agro-morphological Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The lowest weight found was 0.67 g in the SIV-2 genotype, but it too was not significant relative to the other seedlings. Previously, the weight of European Cranberrybush fruit had been reported between 0.40 and 0.87 g (Bolat and Ozcan 1995, Kara et al 1995, Kollmann and Grubb 2002, Karadeniz et al 2003, Cesoniene et al 2010, Ozrenk et al 2011, Gundogar 2013. Large fruit is a desirable quality trait, primarily for the fresh fruits and secondly for the dried ones, rendering them more attractive to consumers.…”
Section: Agro-morphological Characteristicsmentioning
confidence: 99%
“…Cesoniene et al (2010) had reported a wide variation in 10 cultivars and genotypes of European Cranberrybush in Lithuania for the number of fruit per raceme and the number of racemes per bush as 29.6-78.6 (average 46.2) and 228-1039 (average 630), respectively. Ozrenk et al (2011) reported the number of fruit per raceme between 29 and 71 in 2 genotypes of European Cranberrybush grown in eastern Turkey.…”
Section: Agro-morphological Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations